Publicly Funded R&D Collaborations and Patent Outcome in Germany - Dirk Czarnitzki; Andreas Fier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
The stimulation of co-operations and networks has become very popular in R&D policies in recent years. This study examines the development and the impact of publicly funded R&D consortia in Germany. The paper describes the history of R&D funding in Germany with a focus on the development of measures encouraging collaborative R&D activities among firms and public research institutions. Due to a recent shift of policies to more competitive procedures in awarding public funds for R&D, we investigate empirically the impact of such measures on patenting activity at the firm level. The microeconometric results show that collaborating firms are more likely to patent than others. Within the group of collaborating firms, participants in publicly sponsored R&D consortia exhibit a higher propensity to patent than firms in non-sponsored networks. Especially SMEs seem to benefit from spillovers which makes their application for patents more likely.
Keywords: C25; C14; O38; H50; 330; R&D; Public Subsidies; Collaboration; Policy Evaluation; Forschungs- und Technologiepolitik; Forschungskooperation; Forschungssubvention; Wirtschaftspolitische Wirkungsanalyse; Industrielle Forschung; Patent; Schätzung; Deutschland